Measuring and Analyzing The Causal Relationship between Investing Government Expenditure non-oil GDP in Iraq For The Period (1990-2011) - سلمان محمد صالح; حسن نضال قادر (Journal of Economics and Administrative Sciences, 2014)
The investment government expenditure is considered the fundamental of enhancing the economic activity as it has become a mean for achieving capital accumulation in all economic sectors, The Iraqi economy is characterized of being yield unilateral depending petroleum revenues as an essential resource of financing government expenditure , as the contribution of petroleum sector in GDP is large in proportions to other economic sectors contribution. The relationship between investing government expenditure, and non-oil GDP is about to be not existent during the period of the research on the long term, and the reason is the economic sanctions imposed which left negative effects on Iraq economic representing in the decrease of employment levels in the Iraqi sectors , the decrease of productive capacities in commodity sectors ( agricultural - industrial ) and other reasons , After U.S. invasion of Iraq in 2003,new economic features have emerged representing in infrastructure collapse for the most economic and, the decrease of the investments presented to be sustained and expanded for the purpose of their fittnss with population increases and economic and social developments , the continuity yield style of and non- productive of the economic policy trends which contributed in deterioration of commodity sectors , particularly agricultural and industrial , and the accumulation of yield service of Iraqi economy for the benefit of defense and security activities that brought a continuous increase in consumption expenditure at the expense of investing expenditure in productive and development fields ,in addition to that the prevalence of financial and administrative corruption in all economic, managerial and security government activities , and the lack of suitable investing environment that is of a direct role in the decrease of production and hence, the weakness of its contribution in non-oil GDP